Space in modern Egyptian fiction - Ramadan, Yasmine (Edinburgh studies in modern Arabic literature., 2020)
In 1960s Egypt a group of writers exploded onto the literary scene, transforming the aesthetic landscape. Space in Modern Egyptian Fiction explores how this literary generation presents a marked shift in the representation of rural, urban and exilic space, reflecting a disappointment with the project of the postcolonial nation-state in Egypt. Combining a sociological approach to literature with detailed close readings, Yasmine Ramadan explores the spatial representations that embodied this shift within the Egyptian literary scene and the disappearance of an idealized nation in the Egyptian novel. This study provides a robust examination of the emergence and establishment of some of the most significant writers in modern Egyptian literature, and their influence across six decades, while also tracing the social, economic, political and aesthetic changes that marked this period in Egypt's contemporary history.--